Pendugaan Permintaan Pangan Utama di Indonesia: Penerapan Model Almost Ideal Demand System (AIDS) dengan Data Susenas 1990 - Muchjidin Rachmat; nFN Erwidodo (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1993)
This paper aims at presenting the estimation results of an Almost Ideal Demand System (AIDS) for main food namely, rice, corn, soybeans, sugar and other, using 1990's SUSENAS data. In addition to estimating the parameter from the pooled data, the demand parameters were also estimated regionally (urban and rural separately) as well as from household's income perspective. Moreover, the estimation was also undertaken using both individual household and group of household in particular block census as a sample unit. The results reveal that the budget share of rice is more than 80 percent of the total budget expenditure for food, very much higher compared to the budget share of corn (14.6%), sugar (12.6%), soybeans (2.2%) and other food (5.8%). Own price elasticity of rice is the highest among other food, that is 0.76, followed by corn (0.55), and sugar (0.54). Demand for food in rural area, with the exception for sugar, is more elastic than that in urban area. In general, there is a somewhat difference on demand elasticities between income groups. The results also show that the income elasticity of demand for food is elastic enough, indicating that the demand for food in the near future is expected to increase with the increases on household's income.